Comparison of the cleaning efficacy of the FKG race system and hand instrument in molar root canal Comparação da eficácia de limpeza entre o sistema FKG race e instrumentos manuais em molares inferiores - Carla Renata Sipert; Renata Pardini Hussne; Celso Kenji Nishiyama (University of São Paulo, 2006)
INTRODUCTION AND OBJECTIVE: The aim of this study was to evaluate the ability of root canal cleaning of the RaCe rotary instrumentation system (FKG Dentaire - La-Cheaux-de Fonds - Switzerland), compared to manual filing with Stainless Steel K-files (Maillefer Instruments - Ballaigues - Switzerland). MATERIAL AND METHOD: Twenty extracted human teeth (maxillary molars) were selected and their pulp tissue was removed after coronal access. The root canals were filled with a dye (India ink) and allowed to dry for 48 hours, followed by establishment of the working length of the mesiobuccal root; then, half of the specimens were instrumented by the modified Oregon technique and the other half were instrumented by crown-down sequence of the RaCe system. After preparation, the teeth were longitudinally sectioned and evaluated according to the amount of remaining dye. RESULTS: Data obtained were registered as numerical scores, and the arithmetic means were compared between groups using the Mann Whitney test. Both techniques were unable to completely clean the interior of the root canals, with a better performance of the manual technique only at the middle third. CONCLUSION: It could be concluded that the RaCe system was able to provide satisfactory cleaning, similar to that obtained by the manual instrumentation technique. Objetivo deste trabalho foi avaliar a capacidade de limpeza de canais radiculares por meio do sistema de instrumentação RaCe (FKG Dentaire - La-Cheaux-de Fonds - Suíça) em comparação à instrumentação manual por meio de limas tipo K-File (Maillefer Instruments - Ballaigues - Suíça). Foram selecionados 20 dentes humanos extraídos (molares superiores) que tiveram seu conteúdo radicular removido após realização da abertura coronária. Os canais foram preenchidos com corante (tinta nanquim) e após 48 horas para secagem, realizou-se a odontometria da raiz mésio-vestibular. Metade dos espécimes foi instrumentada pela técnica de Oregon modificada e a outra metade pela seqüência crown-down preconizada pelo fabricante do sistema RaCe. Após o preparo, os dentes foram seccionados longitudinalmente e avaliados de acordo com a quantidade de corante remanescente. Os dados obtidos foram registrados por meio de escores numéricos e as médias aritméticas foram analisadas entre os grupos pelo teste de Mann Whitney. Ambas as técnicas foram incapazes de limpar completamente o interior dos canais radiculares sendo que a técnica manual desempenhou limpeza significantemente superior apenas no terço médio. Conclui-se que o sistema RaCe foi capaz de desempenhar uma limpeza satisfatória sendo próxima àquela conseguida pela técnica de instrumentação manual.